Losing the Gains of the Past : The Welfare and Distributional Impacts of the Twin Crises of 2014 in Iraq - World Bank (World Bank, Washington, DC, 2016)
Iraq was plunged into two simultaneous crises in the second half of 2014, one driven by a sharp decline in oil prices, the other, by Islamic State militants. Since June 2014, crude oil prices per barrel have fallen from around 112 USD to 97 USD in September and 62 USD by December. Given Iraq's heavy dependence on oil as a share of GDP and exports, and a source of government revenues, this decline in prices alone would have hit Iraq’s fragile economy hard. In addition, since June 2014, Islamic State (IS) or Da'ash militants extended their influence from Syria into Iraq's northern and western provinces of Anbar, Nineveh, Salahadin, and to a lesser extent, Kirkuk and Diyala. A total of 354,000 families were internally displaced between June and December of 2014 which represents about 2.1 million individuals; and those left behind have been cut off from the rest of the country. The internally displaced persons (IDPs) have sought refuge across Iraq and about half of those who have crossed governorates boundaries were settled in Iraqi Kurdistan.